Genome-Wide Network of lncRNA–mRNA During Ovine Oocyte Development From Germinal Vesicle to Metaphase II in vitro - Wang, Jun-Jie; Niu, Meng-Han; Zhang, Teng; Shen, Wei; Cao, Hong-Guo (Frontiers in Physiology, 2020)
Long non-coding RNA (lncRNA) is involved in many biological processes, and it has been closely investigated. However, research into the role of lncRNA in ovine ovarian development is scant and poorly understood, particularly in relation to the molecular mechanisms of ovine oocyte maturation. In the current study, RNA sequencing was performed with germinal vesicle (GV) and in vitro matured metaphase II (MII) stage oocytes, isolated from ewes. Through the use of bioinformatic analysis, abundant candidate lncRNAs in stage-specific ovine oocytes were identified, and their trans- and cis-regulatory effects were deeply dissected using computational prediction software. Functional enrichment analysis of these lncRNAs revealed that they were involved in the regulation of many key signaling pathways during ovine oocyte development, which was reflected by their targeted genes. From this study, multiple lncRNA–mRNA networks were presumed to be involved in key signaling pathways regarding ovine oocyte maturation and meiotic resumption. In particular, one novel lncRNA (MSTRG.17927) appeared to mediate the regulation of phosphatidylinositol 3-kinase signaling (PI3K) signaling during ovine oocyte maturation. Therefore, this research offers novel insights into the molecular mechanisms underlying ovine oocyte meiotic maturation regulated by lncRNA–mRNA networks from a genome-wide perspective.